Aging‐related metabolic changes in the extensor digitorum longus muscle of senescence‐accelerated mouse‐prone 8. Issue 2 (22nd December 2021) - Hoshino, Teruhide; Kato, Yoshiaki; Sugahara, Keisuke; Katakura, Akira
Abstract : Aim: Sarcopenia – aging‐related loss of muscle mass and muscle strength – is a key feature of the frailty model. In the present study, we aimed to elucidate the molecular biological changes associated with aging in the extensor digitorum longus muscle of senescence‐accelerated mouse prone 8 mouse model by capillary electrophoresis–mass spectrometry. Methods: Three groups of senescence‐accelerated mouse prone 8 mice were used, namely, 12‐week‐old (young; n  = 5), 40‐week‐old (elderly; n  = 5) and 55‐week‐old mice (late elderly; n  = 5). The extensor digitorum longus muscle was collected. After preliminary analyses, metabolome analysis was carried out by capillary electrophoresis–mass spectrometry. Additionally, we examined whether the activity of enzymes in the metabolic pathway fluctuated with aging, by real‐time polymerase chain reaction. Results: Among the 116 water‐soluble metabolites associated with the central energy metabolism pathway, changes were observed in 19 metabolites between 12‐ and 40 ‐weeks‐old, in 40 metabolites between 40‐ and 55‐weeks‐old, and in 57 metabolites between 12‐ and 55‐weeks‐old. The fluctuated metabolites that were common among the groups were Val, putrescine and His. The levels of putrescine, associated with cell proliferation, protein synthesis and nucleic acid synthesis, and β‐Ala and His, a component of carnosine that is characterized by its anti‐oxidant and anti‐fatigue effects, decreased with age. Conclusions: We confirmed that there were two aging‐related metabolic changes in the extensor digitorum longus muscle of senescence‐accelerated mouse prone 8 mice. Based on the changes in metabolites, cell senescence and fatigue in the extensor digitorum longus muscle might increase in old mice compared with those in young mice, showing molecular biological changes with aging. Geriatr Gerontol Int 2022; 22: 160–167 .